2014
DOI: 10.1038/cmi.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Liaison between natural killer cells and dendritic cells in human gestation

Abstract: A successful pregnancy relies on immunological adaptations that allow the fetus to grow and develop in the uterus, despite being recognized by maternal immune cells. Among several immunocompetent cell types present within the human maternal/fetal interface, DC-SIGN 1 dendritic cells (DCs) and CD56 1 natural killer (NK) cells are of major importance for early pregnancy maintenance, not only generating maternal immunological tolerance but also regulating stromal cell differentiation. Previous reports show the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 65 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…In normal human decidua, both immature myeloid—identifiable by their expression of DC‐SIGN (CD209)—and mature myeloid DCs coexist . In early human pregnancy, the presence of DC‐SIGN+ cells and dNK clusters indicates that the interconnection between these cell subsets is essential in pregnancy maintenance . In fact, dNK cells induce apoptosis in DC‐SIGN+ cells, constituting a mechanism of maternal‐foetal tolerance .…”
Section: Decidual Immune Cells and T Gondii Infectionmentioning
confidence: 99%
“…In normal human decidua, both immature myeloid—identifiable by their expression of DC‐SIGN (CD209)—and mature myeloid DCs coexist . In early human pregnancy, the presence of DC‐SIGN+ cells and dNK clusters indicates that the interconnection between these cell subsets is essential in pregnancy maintenance . In fact, dNK cells induce apoptosis in DC‐SIGN+ cells, constituting a mechanism of maternal‐foetal tolerance .…”
Section: Decidual Immune Cells and T Gondii Infectionmentioning
confidence: 99%
“…In the cycling human endometrium, mature dendritic cells (DCs) are at their peak at the late secretory phase, in contrast with early pregnancy decidua, where the majority of the DCs express CD209 (DC-SIGN), a marker of immature or inactive DC (Gardner and Moffett 2003 ;Kammerer et al 2003 ;Rieger et al 2004 ). Although it has been suggested that DCs may play a role in remodelling the cycling endometrium following menstruation, current attention is focused on their potential role in the modulation of immune responses within the pregnant uterus (Dietl et al 2006 ;Blois et al 2011 ;Leno-Durán et al 2014 ) with increasing interest into their potential interactions with uNK cells.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Activated NK cells regulate the following actions of DCs: cytokine-producing capacity; Th-cell polarizing ability; chemokine expression; migration, editing and maturation; and stimulatory functions. On the other hand, activated DCs are required for the execution of innate and effector functions of NK cells including NK cell differentiation [79][80][81][82][83][84]. NK cells and DCs mutually in luence each other and the bidirectional crosstalk between the 2 components of the innate immune system, that may be well coordinated, plays a pivotal role in the regulation of immune defense against viruses such as CMV, parasites such as Leishmania amazoneasis, and tumors [80,82,[85][86][87][88][89][90].…”
Section: Interactions Between Nk Cells and Other Immune Cellsmentioning
confidence: 99%